A case of Fournier's gangrene diagnosed with POCUS - Marco Badinella Martini; Antonello Iacobucci (CINQUILL Medical Publishers Inc., 2019)
An 87-year-old man with a history of type 2 diabetes and severe Alzheimer disease was admitted to the emergency department with a lesion of the perineum for two days. The patient appeared agitated and not collaborating on the visit. His vital signs were normal. Physical examination revealed an edematous, suppurative, and foul-smelling perineal-scrotal lesion, with possible subcutaneous emphysema.